2019
DOI: 10.1002/cphc.201900447
|View full text |Cite
|
Sign up to set email alerts
|

Functional Metal Oxides in Perovskite Solar Cells

Abstract: As extremely important inorganic materials, metal oxides play an irreplaceable role in solid perovskite solar cells. In this review, the preparation methods of metal oxides, their effects on the perovskite optoelectronic devices incorporated with the energy level compatibility of perovskite materials are provided. Finally, the possible reactions between interfaces during growth progress as well as passivation mechanism of some metal oxides to perovskite materials are discussed. The physical, chemical, and elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 68 publications
(102 reference statements)
0
35
0
Order By: Relevance
“…The compact TiO 2 layer can be produced by spray pyrolysis, thermal oxidation, atomic layer deposition, and electrochemical deposition. [ 48 ] But, during the fabrication process of TiO 2 , a high‐temperature annealing process (even up to 450 °C) is essential and hinders its application on different substrates. Thus, inorganic SnO 2 and ZnO ETLs are developed that could be prepared at low temperatures.…”
Section: Materials For Csbx3 Pscsmentioning
confidence: 99%
“…The compact TiO 2 layer can be produced by spray pyrolysis, thermal oxidation, atomic layer deposition, and electrochemical deposition. [ 48 ] But, during the fabrication process of TiO 2 , a high‐temperature annealing process (even up to 450 °C) is essential and hinders its application on different substrates. Thus, inorganic SnO 2 and ZnO ETLs are developed that could be prepared at low temperatures.…”
Section: Materials For Csbx3 Pscsmentioning
confidence: 99%
“…For many of those new technologies, widespread implementation hinges on targeted development of engineered materials to improve performance, efficiency, and cost. Metal oxides provides opportunity for such an approach and have been investigated for many applications, such as catalysis, 2 active materials in solar cells, 3 batteries, 4,5 electrochromic applications, 6 and (pseudo-)capacitors. 7 Crystalline (or poly-crystalline) metal oxides have traditionally been utilized.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that some complex oxides have ferromagnetic, ferroelectric, and magnetoresistive effects, which allows complex oxides to be implemented into important applications in the field of microelectronics. For example, amorphous a-IGZO [103] and perovskite metal-oxides [104], have been exploited to facilitate the advancement of microelectronics under the bottleneck of Moore's law.…”
Section: Complex Metal Oxidesmentioning
confidence: 99%